Cobalt-catalyzed highly enantioselective hydrogenation of α,β-unsaturated carboxylic acids - Xiaoyong Du (Nature Portfolio, 2020)
A large number of marketed drugs contains a chiral carboxylic acid scaffold. Here, the authors report the asymmetric hydrogenation of α,β-unsaturated carboxylic acids to α-chiral carboxylic acids using a cobalt catalyst bearing an electron-donating chiral diphosphine ligand.